Athlete's dependence and acceptance on the language of health article writing in the press - Hassan, Mohd Hazreen Shah; Shari, Sharil Nizam; Ahmad Ghazali, Akmar Hayati; Hamzah, Zaitul Azma Zainon; Ismail, Alhaadi; Ayub, Nur Afiqah (Human Resource Management Academic Research Society, 2021)
Malaysians today are beginning to realize the importance of improving their health both physical fitness and mental intelligence. Nowadays, the press is one of the mediums that can be accessed by the public to obtain health information through health articles. Therefore, this study was conducted to examine the extent to which athlete’s dependence on newspaper health articles to obtain information related to health aspects as well as their acceptance of the language used of health article writing in newspapers. This study uses two methods, namely field study (80%) and content analysis (20%). The research tool in this study is a questionnaire, distributed to 50 respondents consisting of university / state and national athletes. The findings of the study show that the dependence of athletes on health articles in the press is at an excellent level with a mean score of 4.24 (standard deviation: 0.65). Besides, the level of acceptance of athletes towards the language used of health articles writing in the press is at a good level, with a mean score of 4.09 (standard deviation: 4.41). These findings indicate that the newspaper is an option among athletes to obtain information related to health, and the language used in the newspaper is easy to understand and able to influence their cognition, feelings, and behavior.